2018
DOI: 10.1097/sla.0000000000003109
|View full text |Cite
|
Sign up to set email alerts
|

Classifying Preoperative Opioid Use for Surgical Care

Abstract: Objective: We characterized patterns of preoperative opioid use in patients undergoing elective surgery to identify the relationship between preoperative use and subsequent opioid fill after surgery. Background: Preoperative opioid use is common, and varies by dose, recency, duration, and continuity of fills. To date, there is little evidence to guide postoperative prescribing need based on prior opioid use. Methods: We analyzed claims data from Clinformatics® DataMart Database for patients aged 18-64 years un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 32 publications
1
48
0
1
Order By: Relevance
“…As such, prescribing restrictions based on number of days alone or number of doses may miss important nuances of perioperative care, such as prior opioid exposure, procedure type, and patient-level risk factors. 24 An alternative approach to reduce excessive prescribing may be to develop and implement evidence-based prescribing guidelines based on patient-reported opioid-related outcomes, including opioid consumption, use of opioid alternatives, pain, and satisfaction. 3,[16][17][18] For example, Hill et al 17 developed opioid prescribing guidelines based on the amount consumed while being an inpatient to direct the amount prescribed for outpatient pain control after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…As such, prescribing restrictions based on number of days alone or number of doses may miss important nuances of perioperative care, such as prior opioid exposure, procedure type, and patient-level risk factors. 24 An alternative approach to reduce excessive prescribing may be to develop and implement evidence-based prescribing guidelines based on patient-reported opioid-related outcomes, including opioid consumption, use of opioid alternatives, pain, and satisfaction. 3,[16][17][18] For example, Hill et al 17 developed opioid prescribing guidelines based on the amount consumed while being an inpatient to direct the amount prescribed for outpatient pain control after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The secondary outcome was the odds of an initial fill, defined as filling a postoperative opioid prescription between 14 days before admission and 3 days after discharge. [19][20][21][22][23] Opioid prescription fills and refills were identified in Medicare Part D Prescription Drug Event data using National Drug Codes and converted to oral morphine equivalents using Centers for Disease Control conversion factors. 24…”
Section: Discussionmentioning
confidence: 99%
“…Patients who filled prescriptions within the period between 12 months and 15 days before admission but did not meet the criteria of chronic user were classified as intermittent opioid users. 19 The initial postoperative opioid prescription size, in 10 tablets of 5 mg oxycodone, was also included as a covariate.…”
Section: Patient Covariatesmentioning
confidence: 99%
“… 69 Opioid prescribing has increased significantly and excessive opioid prescribing is prevalent, particularly after surgical care. 70 Liver transplant patients represent a population vulnerable to opioid exposure given the prevalence of substance use disorders and the associated risk of opioid misuse. 71 Indeed, a recent review of opioid use while on the transplant waiting list and following transplant revealed concerning trends.…”
Section: Pain Management In Ltmentioning
confidence: 99%